Mutually supportive implementation of the Nagoya Protocol and the Plant Treaty: Scenarios for consideration by national focal points and other interested stakeholders. - Joint Capacity Building Programme (2017)
Bioversity International works with a wide range of international and national partners to implement the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) and the Nagoya Protocol of the Convention on Biological Diversity in mutually supportive ways.